The Western Australian Police headquarters building: Surveillance, power and the authoritarian state - Stratton, Jon (UTS ePress, 2013)
The building housing the Police Headquarters in East Perth, at the eastern gateway to the city of Perth, was opened in 1975. Through the fifteen years it took to be constructed Western Australia, primarily under two Liberal premiers, David Brand and Charles Court, was transformed into a state founded on resource extraction and export. Paralleling this development, Western Australia’s government became increasingly authoritarian and its policing was more and more tied to the needs of that government. All this is expressed in the positioning and architectural style of the Police Headquarters. Michel Foucault has argued that surveillance was a key aspect of the modern world. The Police Headquarters can be read also as expressing the form of mass surveillance which typified modernity, a surveillance which can easily work in tandem with the authoritarian state.